Problem solving using manipulatives in elementary mathematics - Tabil, Rey D. (2006)
This study is a quasi-experimental research involving two approaches on teaching problem-solving in elementary mathematics. It sought to determine which of the two approaches, the manipulatives and conventional way of teaching, would have a better effect on achievement and retention of concepts taught. Twenty-four pairs from two Grade 6 classes were taught using lesson plans with the same instructional content but with different approaches. Other sources of data were the achievement test and delayed posttests, and a class observation. Observations revealed that students from the experimental group showed greater interest in classroom participation and manifested positive attitudes in learning mathematical concepts using the hands-on manipulatives.
"March 2006."
Thesis (M.A.Education : Elementary Mathematics)--University of the Philippines, Diliman.
Keywords: Problem solving -- Study and teaching (Elementary) -- Philippines -- Misamis Oriental; Mathematics -- Study and teaching (Elementary) -- Philippines -- Misamis Oriental -- Audio-visual aids; Manipulatives (Education) -- Philippines -- Misamis Oriental